Resilience and parental socialization styles in students of 4th and 5th year of high school in Lima Metropolitana - Bulnes B., Mario (2008)
Objectives: 1) To establish the psychometric properties of the instruments used; 2) To analyze the relationship between resilience and styles of parental socialization variables in fourth and fifth grade hight school students considering public and private schools; 3) To compare the resilience variable in fourth and fifth grade hight school students between public and private school; 4) To compare the variable resilience in fourth and fifth grade hight school students between gender; 5) To compare the parental socialization styles variable in fourth and fifth grade hight school students between public and private school; 6) To compare the parental socialization styles variable in fourth and fifth grade hight school students between gender. Type and design: It is a basic research, with a descriptive, correlation and comparative design. Materials and methods: The sample was made up of 394 fourth and fifth grade hight school students, of whom 189 are from public schools and 205 from private schools of Lima city. To this end we used the Scale of resilience of Wagnild & Young (1993), and the scale of parental socialization styles in adolescent, of Musitu & Garcia (2001). Results: As a result of the study was found reliability and validity of the instruments used, in addition there was a significant correlation between these two variables, and equally significant differences in both variables taking into account gender and type of school.